A Comparative Study of Health Promotion Networks: Configurations of determinants for network effectiveness. Issue 8 (13th September 2016) - Lucidarme, Steffie; Cardon, Greet; Willem, Annick
Abstract: Collaborative public networks have become increasingly important as policy tools to address complex social and health problems. However, despite the broad literature on network effectiveness, there is still insufficient insight into the different determinants of whole network effectiveness, and particularly on how these determinants are related. Based on an empirical comparison of 13 mature networks, this study identified potential environment, structural, and management determinants. Moreover, configurations of the identified determinants leading to network effectiveness were generated using configurational comparative methods. We gained insights into how configurations of determinants impacted network effectiveness and found a dominance of structural and managerial determinants.